Clinical Characteristics and Outcomes of Severe Pneumonia in Children Under 5 Years Old With and Without Adenovirus Infection in Guangzhou - Lingling Zheng (Frontiers Media S.A., 2021)
Objectives: To identify the differences of clinical characteristics and outcomes of severe pneumonia in children under 5 years old with and without adenovirus infection.Methods: A retrospective cohort study was conducted in three pediatric hospitals in Guangzhou, China. In total, 1,595 children under the age of 5 with WHO-defined severe pneumonia had adenovirus testing performed between January 1, 2009 and December 31, 2019. Demographics, complications, the first routine laboratory findings, therapeutic records, and clinical outcome were collected from electronic medical records. We compared characteristics of children with and without adenovirus infection.Results: Adenovirus was detected in 75 (4.7%) out of 1,595 children with severe pneumonia. Cases with adenovirus infection were more likely to be boys (74.7 vs. 63.0%), older than 1 year old (78.7 vs. 25.1%), but less likely to have mixed virus infections (25.3 vs. 92.9%) and combined with cardiovascular disease (12.0 vs. 39.7%), and had more abnormal laboratory results than cases without adenovirus infection. Antiviral therapy (4.9%) was rarely used in children with severe pneumonia, but antibiotic therapy (65.3%) was commonly used, especially in cases with adenovirus infection (91.9%). Children infected with adenovirus (9.3 vs. 2.5%) were also hospitalized longer and had a higher mortality within 30 days of hospitalization.Conclusions: Children with severe pneumonia under 5 years old with adenovirus infection had more abnormal laboratory findings and more severe clinical outcomes than cases without adenovirus infection. More attention should be focused on the harm caused by adenovirus infection.